Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick pada Siswa - Lestari, Juliana Sinta; Hamdan, Hamdan; Andita, Cahyo Dwi (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to determine the completeness of the learning outcomes of Pancasila Education of fourth-grade students of SD Negeri 54 Lubuklinggau after the implementation of the talking stick type cooperative learning model in the Pancasila education subject. The research method used is pre-experiment design. The population is all fourth-grade students of SD Negeri 54 Lubuklinggau and the research sample is 20 students. Data collection is carried out using a test technique consisting of 13 questions. Based on the results of the analysis, the average Pre-Test is 36.9 and the average Post-Test is 88.1. The collected analysis results are analyzed using a t-test, the amount of Thitung = 13.50 and Ttabel = 1.64, because Thitung = 13.50 ≥ Ttabel = 1.64 then H₀ is rejected and Ha is accepted. So it can be concluded that the learning outcomes in learning Pancasila Education of fourth-grade students of SD Negeri 54 Lubuklinggau after the implementation of the Talking stick learning model are significantly complete.   Keywords: Learning Outcomes, Talking stick , Pancasila Education